2009
DOI: 10.1007/s12237-009-9160-1
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation Potential of Estuarine Particles: The Importance of Environmental Factors and of the Spatial and Seasonal Variability of Suspended Particulate Matter

Abstract: International audienceEstuarine systems are complex environments where seasonal and spatial variations occur in concentrations of suspended particulate matter, in primary constituents, and in organic matter content. This study investigated in the laboratory the flocculation potential of estuarine-suspended particulate matter throughout the year in order to better identify the controlling factors and their hierarchy. Kinetic experiments were performed in the lab with a “video in lab” device, based on a jar test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 38 publications
0
84
1
4
Order By: Relevance
“…In wet season in the Yangtze Estuary, Guo et al [84] reported d f values varying between 1.5 and 2.1 (around a best fit = 1.8). Based on measurements in the Seine estuary, Verney et al [89] reported d f values between 1.62 and 1.82, with a mean of 1.75. From observations of particle cross-sectional area and mass performed along the south and west coasts of Great Britain, Bowers et al [90] showed that d f varied in the range 1.9-2.7.…”
Section: Fractal Dimensionmentioning
confidence: 99%
“…In wet season in the Yangtze Estuary, Guo et al [84] reported d f values varying between 1.5 and 2.1 (around a best fit = 1.8). Based on measurements in the Seine estuary, Verney et al [89] reported d f values between 1.62 and 1.82, with a mean of 1.75. From observations of particle cross-sectional area and mass performed along the south and west coasts of Great Britain, Bowers et al [90] showed that d f varied in the range 1.9-2.7.…”
Section: Fractal Dimensionmentioning
confidence: 99%
“…with a Kolmogorov microscale greater than 1000 µm) (Verney et al, 2009), and turbulence has been identified as the most important factor controlling aggregation in the wet season in the Bach Dang estuary . Apart from the sediment load, sediment deposition in the estuary is governed by hydrodynamics (Q and turbulence).…”
Section: Enhanced Estuarine Depositionmentioning
confidence: 99%
“…The experiments were carried out in two main steps: The first step is to apply the highest tested shear stress of 60 N/m 2 to break down any potential macroflocs in suspension as the initial state; the second step, which is the main testing part, is to run the agitator at a series of rotational speeds to generate the desired turbulent shear stresses, ranging from 0.57 N/m 2 to 8.55 N/m 2 for a duration of 120 min as suggested by (Mikes et al 2004;Verney et al 2009). This is a significant time period for flocculation to occur in natural water bodies (Le Hir et al 2001), where the average floc size no longer changes after this time.…”
Section: Methodsmentioning
confidence: 99%
“…Floc size was obtained using the contrast between the dark background and the white silhouettes of the floc. The surface equivalent diameter d was calculated by converted particle area ( ) into equivalent circular diameter (Flory et al 2004;Mikes et al 2004;Verney et al 2009) as:…”
Section: Image Analysismentioning
confidence: 99%